Subharmonics of a Nonconvex Noncoercive Hamiltonian System - Kallel, N.; Timoumi М. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We study the problem of the existence of multiple periodic solutions of the Hamiltonian system Jx + u abla G( t,u( x ) ) = e( t ), where u is a linear mapping, G is a C 1-function, and e is a continuous function.